MOLLUSCA DIVERSITY BASED ON HABITATE CHARACTERISTICS ON SUJONO BEACH, BATU BARA DISTRICT, NORTH SUMATERA - Nurfadilah Nurfadilah; Abdul L. Mawardi; Elfrida Elfrida (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2021)
Mollusca is a soft-bodied fauna that is widespread in various habitats including sand, mud and coral substrates. The purpose of this study was to determine the diversity of Mollusca based on habitat characteristics at Sujono Beach, Batu Bara Regency, North Sumatra. This research was conducted at Sujono Beach, Batu Bara Regency, North Sumatra. Sampling was conducted in February 2021. Sampling was carried out by purposive sampling method based on Mollusca habitat. The results showed that the diversity of Mollusca was in the medium category with a value of H '= 1.0048. The most preferred habitat for Mollusca is on sandy substrates, while the habitat that Mollusca does not like is coral substrate.